Pemanfaatan kunyit (Curcuma domestica Val) sebagai imunostimulan pada ikan bawal (Colossoma macropomum) - Manurung, Usy N.; Mose, Numisye I. (e-Journal BUDIDAYA PERAIRAN, 2019)
This study was conducted to evaluate the effectiveness of turmeric (Curcuma domestica Val) as an immunostimulant in pomfret (Colosoma macropomum). The test fish were pomfret as much as 150 individuals having an average of 28.78 Â± 2.44 g. After acclimatization process, the fish were given turmeric as a treatment with five different doses, each with three replications. The treatments used were A = 0 g, B = 5 g, C = 10 g and D = 15 g turmeric/kg of feed. Duration of feeding was two weeks at a dose of 5%/body weight/day, twice a day at 08.00 am and 16.00 pm. The results obtained showed that the application of turmeric had a significant effectÂ  on the total leukocyte of pomfret(P <0.01). Application of turmeric at 15 g/kg of feed proved to be able to increase the number of leukocytes in pomfret. Keywords: Curcuma domestica Val, leukocyte, immunostimulant, growth